Overreaction of Equity and Fixed Income ETF during the 2007/2008 Financial Crisis - Ana Isabel Vilaça da Costa (2017)
The financial crisis of 2007/2008 is considered one of the most important event in the history of financial markets, leading to a significant change in the perspective of investors. Since then, investors look to mitigate their exposure to credit risk, given preferences for instruments like exchange traded funds (ETF) which are characterized by low specific credit risk. Therefore, ETF markets have been growing significantly since the financial crisis. Together with this growth, increases the relevance of studying the price dynamics experienced by this market. With this study we intend to make an additional contribution in this topic through the analysis of the equity and fixed income ETF market on the US. More specifically, we study the patterns of overreaction of the equity and fixed income ETF markets in the period 2007-2014. Moreover, as far as we know there are not studies approaching overreaction on fixed income ETF market. In a complementary basis, we also analysis financial crisis and recovery periods as well as bull and bear market periods, separately. Overall, we found higher degree of overreaction during the periods in which the market is closed (after-hours periods) then during market sessions which could be justified by the lower liquidity level and the proportion of informed traders to noise traders in after-hours periods. We also found significant differences between financial period and recovery periods as well as between bull and bear periods. However, it is important to point out that such results could be influenced by the very unique period on financial market history approached. On the other hand, the overreaction is inferred based on the first 24 hours following the extreme price movements occur, longer reversals are not captured by this study. Regarding fixed income market, a low level of development could also influence the results obtained. Forthcoming analysis using other time range and other regional markets could be a relevant for this topic.